Biofilm Formation, Production of Matrix Compounds and Biosorption of Copper, Nickel and Lead by Different Bacterial Strains - Haque, Md. Manjurul; Mosharaf, Md Khaled; Haque, Md. Amdadul; Tanvir, Md. Zahid Hasan; Alam, Md. Khairul (Frontiers in Microbiology, 2021)
Bacterial biofilms play a key role in metal biosorption from wastewater. Enterobacter asburiae ENSD102, Enterobacter ludwigii ENSH201, Vitreoscilla sp. ENSG301, Acinetobacter lwoffii ENSG302 and Bacillus thuringiensis ENSW401 were shown to form air-liquid (AL) and solid-air-liquid (SAL) biofilms in a static condition at 28°C and 37°C, respectively. However, how environmental and nutritional conditions affect biofilm formation, production of curli and cellulose, and biosorption of copper (Cu), nickel (Ni) and lead (Pb) by these bacteria have not been studied yet. In this study, E. asburiae ENSD102, E. ludwigii ENSH201 and B. thuringiensis ENSW401 developed the SAL biofilms at pH 8.0, while E. asburiae ENSD102 and Vitreoscilla sp. ENSG301 constructed the SAL biofilms at pH 4.0. However, all these strains produced AL biofilms at pH 7.0. In high osmolarity and ½ strength media, all these bacteria built fragile AL biofilms, while none of these strains generated the biofilms in anaerobic conditions. Congo red binding results showed that both environmental cues and bacterial strains played a vital role in curli and cellulose production. Calcofluor binding and spectrophotometric results revealed that all these bacterial strains produced significantly lesser amounts of cellulose at 37°C, pH 8.0 and in high osmotic conditions as compared to the regular media, at 28°C, and pH 7.0. Metal biosorption was drastically reduced in these bacteria at 37°C than at 28°C. Only Vitreoscilla sp. ENSG301 and B. thuringiensis ENSW401 completely removed (100%) Cu and Ni at initial concentration of 12.5 mg L-1, while all these bacteria totally removed (100%) Pb at concentrations of 12.5 and 25 mg L-1 at pH 7.0 and 28ºC. At initial concentration of 100 mg L-1, the removal of Cu (92.5 to 97.8%) and Pb (89.3 to 98.3%) was the highest at pH 6.0, while it was higher (84.7 to 93.9%) for Ni at pH 7.0. Fourier transform infrared spectroscopy results showed metal unloaded biomass biofilms contained amino, hydroxyl, carboxyl, carbonyl and phosphate groups. The peak positions of these groups were shifted responding to Cu, Ni and Pb, suggesting biosorption of metals. Thus, these bacterial strains could be utilized to remove Cu, Ni and Pb from aquatic environment.